Dairy cattle feed options and practices in Ethiopia - Duncan, Alan J.; Greiling, J. (International Livestock Research Institute, 2011)
Alan Duncan of ILRI and Jürgen Greiling of SNV Ethiopia reflect on a 'fodder roundtable' held at ILRI on 27 January 2011. The meeting discussed and evaluated current practices of feeding dairy cattle in Ethiopia.